Unformatted text preview: c 3 = c 4 = 0 and get y p ( t ) = cos t ln  cos t  + t sin t. Thus a general solution to the given equation is y ( t ) = y p ( t ) + y h ( t ) = cos t ln  cos t  + t sin t + c 1 cos t + c 2 sin t. 3. First, we can simpli±y the equation by dividing both sides by 2. This yields x − x − 2 x = e 3 t . 213...
View
Full
Document
This note was uploaded on 03/29/2010 for the course MATH 54257 taught by Professor Hald,oh during the Spring '10 term at Berkeley.
 Spring '10
 Hald,OH
 Math, Differential Equations, Linear Algebra, Algebra, Equations

Click to edit the document details